Project-Based Learning E-Module: Analysis of Student Response and Its Correlation to Responsible and Independent Characters - Dwi Agus Kurniawan; Febri Tia Aldila; Endah Febri Setiya Rini; Rahmat Perdana; Andriyanto Andriyanto (Journal of Innovation in Educational and Cultural Research, 2025)
This research aims to examine students' responses to implementing PjBL-based e-modules and their correlation with responsible and independent characters. A quantitative approach was employed, involving a sample of 68 eighth-grade students from SMP Adhyaksa 1 Jambi and SMP Dharma Bhakti 3 Jambi, selected through purposive sampling. The study utilized research instruments such as student response questionnaires regarding PjBL-based e-modules, responsible character questionnaires, and independent character questionnaires. Data were analyzed using t-tests and correlation tests. The findings indicate significant differences between the two schools regarding student responses to PjBL-based e-modules, responsibility, and independence. A significant correlation was found between students' responses to PjBL-based e-modules and their responsible characters, responses to PjBL-based e-modules and independent characters, and between responsible and independent characters within each school. The study concludes that student responses to PjBL-based e-modules correlate with their character development. These results enhance teaching and learning through technology, ultimately fostering positive character formation among students.